Scaling up Multisectoral Approaches to Combating HIV and AIDS - Gillespie, Stuart; Kadiyala, Suneetha; Binswanger-Mkhize, Hans P. (International Food Policy Research Institute, 2006)
The AIDS pandemic is a global crisis with impacts that will be felt for decades to come, demanding massive responses at many levels. Such responses need to continue to be grounded in the three core pillars of prevention, care and treatment, and mitigation. But these responses need to be much larger in scale, far more broadly based, and better connected so as to better match the scale, breadth, and interconnectedness of the pandemic’s causes and impacts.